Structure and Vibrational Spectra of Benzidine - Akalın, Elif; AKYÜZ, SEVİM (Elsevier, 2003)
The geometry and vibrational spectrum of benzidine have been computed by ab initio calculations using the DFT/B3LYP method with 6-31+G(d,p) basis set. In the most stable geometry, the dihedral angle between the two phenyl rings was found to be around 38°. Calculated wavenumbers were scaled by a single factor 0.965 to approximately correct for vibrational anharmonicity as well as for overestimation of the force constants. Normal coordinate analysis of benzidine and some of its deuterated derivatives have also been performed in valance force field approximation in order to demonstrate the transferability of the force field of aniline. Good agreements between the two different calculation results (ab initio and force field refinement methods) and between the calculated and observed values are found.
Keywords: Benzidine; Wavenumbers; Ab Initio Calculations; Normal Coordinate Analysis